2017
DOI: 10.1007/s13337-017-0414-4
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of H120 and Ma5 avian infectious bronchitis vaccines in early challenge against QX strain

Abstract: Infectious bronchitis (IB) is a highly infectious avian pathogen, which affects the respiratory tract, gut, reproductive system, and kidney of chicks of all ages. Many different serotypes of IB virus (IBV) are recognized which cause different clinical manifestations. According to the antigenic differences, different serotypes of the virus do not cross-protect. Massachusetts serotype induces the best cross-protection against other serotypes. Recently, the IBV QX strain has been detected in Iran. QX strain cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Currently, QX-like IBV is the predominant genotype of IBV in Thailand [2]. The spread of QX-like IBV is controlled through the use of live attenuated vaccines, which is difficult because different serotypes of vaccines do not provide adequate protection [17,18]. Therefore, rapid detection of the virus within an infected chicken flock is important for controlling QX-like IBV outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, QX-like IBV is the predominant genotype of IBV in Thailand [2]. The spread of QX-like IBV is controlled through the use of live attenuated vaccines, which is difficult because different serotypes of vaccines do not provide adequate protection [17,18]. Therefore, rapid detection of the virus within an infected chicken flock is important for controlling QX-like IBV outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some IBV strains can provide cross-protection against other serotypes [ 10 ]. In many studies, these IBV strains are identified as protectotype strains [ 11 25 26 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies of chickens vaccinated with the Mass vaccine strain, the most commonly used IB vaccine could not provide adequate protection against the field IBV Belgian B1648 strain [ 9 ], Holland D1466, South Africa 890/80, Brazil 50/96 [ 10 ], Iranian QX-like [ 11 ], and Thai QX-like [ 12 ]. In another study, chickens vaccinated with the variant IB 4/91 vaccine showed poor protection against local IBV Holland D1466, South Africa 890/80, and Honduras 22/97 strains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 93% clinical protection effects against the QX-like strain was generated by administration of the polyvalent vaccine C at 1 D of age and the polyvalent vaccine B at 10 D of age, whereas the boost of vaccination was changed in group 3, and only 80% protection rate was provided ( Table 2 ). At present, no study has demonstrated the mechanism about the change of protection effect that was based on changing the boost of vaccination ( Karimi et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had showed that a single vaccine with different serotype affords less protection against QX-like and TW-like IBV strains ( Gao et al., 2016 ; Karimi et al., 2018 ). Despite the development of homologous vaccines was often impractical, immunization with multiple serotype vaccines had been proven to be beneficial and broadened the protective spectrum (i.e., “protectotype concept”) ( Cook et al., 1999 ; Zhao et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%